Imperial Rule in Medieval Spain: Christian and Islamic Contexts. (October 2017) - Drews, Wolfram
With the coronation of Alfonso VII of Léon and Castile as 'emperor of all Spain' in Toledo in 1135 the imperial aspirations of the Leonese kings reached a climax. Their origins, however, go back to the tenth century, when individual kings were called 'imperator' in charters. This article traces the origins of this tradition within the context of political history and outlines the phenomenon of imperial self-ascriptions on the Iberian Peninsula. While modern research traditionally focused on the question of whether or not the kings of León pursued an 'imperial programme' and, if they did, what fundamental ideas lay behind such a programme, this article proposes a different approach: by focusing on the interdependencies between Christian and Muslim powers, it argues that the coronation of Alfonso VII could have been a direct response to the proclamation of 'Abd al-Mu'min as caliph of the Almohad Empire in 1132. A close analysis of the royal and imperial titles already used by Alfonso's grandfather Alfonso VI shows that he imitated the traditional caliphal title to be 'ruler of the faithful', although religious references were not a traditional part of Christian imperial titles. By examining Leonese and Almohad imperial self-ascriptions, the article offers a model by which we can explore the ways in which neighbouring imperial powers influenced each other and developed competing claims to power. The article establishes that Christian use of imperial titles on the Iberian Peninsula came to an abrupt end once competition with Muslim rivals became obsolete. It underlines the importance of the individual context in which a title was used, a point that stands in stark contrast to the received view that there was an unchanging 'conceptual core' to the notion of 'empire' as it was used by the peninsula's kings. The article also highlights the hegemonic connotations of imperial notions in medieval Iberia and the importance of a motif of rulership that included subjects of both Christian and Muslim belief.